Lithological modelling based on shear wave velocity using horizontal to vertical spectral ratio (HVSR) inversion of ellipticity curve method to mitigate landslide hazards at the main road Of Samigaluh District, Kulon Progo Regency, Yogyakarta - Widyadarsana Skolastika Novita (EDP Sciences, 2021)
Many landslides occur in Samigaluh District, Kulon Progo Regency, Yogyakarta, Indonesia. However, no research discusses landslides that often occur on the main road connecting the city of Yogyakarta and various tourist resorts in Samigaluh. This study aims at determining the soil vulnerability and lithology model at that main road as a contribution to landslide mitigation planning. This lithology model is based on shear wave velocity (Vs) and layer thickness derived by microtremor datasets. The data were processed by the inversion of the Horizontal to Vertical Spectral Ratio (HVSR) technique of the ellipticity curve method. The result of the study shows that the first layer is associated with topsoil which has Vs of 263 m/s, the second layer is clay which has Vs of 607 m/s, the third layer consists of clay, breccia, and pumice which has Vs of 1119 m/s, and the fourth layer is andesite bedrock which has Vs of 1721 m/s. Andesite is impermeable to water and can become a slip field for landslides. Clay, breccias, and pumice can absorb water so that their weight increases when it rains. When they are on an impermeable rock on a certain slope, a landslide occurs.